A reestruturação das cadeias de suprimentos de sementes de milho híbrido no Brasil - Dias, Fernando Mayer (2007)
The changes in the supply and in the products demand have motivated the companies to look for new ways of management, able to integrate the organizations, based on the development of relationships with business partners. In the hybrid corn seeds sector in Brazil, this search started in the end of nineties, when this sector was restructured, creating a new hybrid supply in the market and raising the competition. The higher products supply associated with the changes in the seeds demand profile has resulted in difficulties for the processors to establish the mix in order to serve the farmers, creating wastes in obsolete stock forms. This paper proposes a study of multiple cases in order to clarify casual links between the supply chain structure and the obsolete seeds wastes. The participant members, the structural dimensions, the integrations of the demand management process and the products and information flows were all identified. The results of this research point out that the national hybrid corn seeds sector shows two distinct supply chain structures. A traditional structure, that counts on the presence of the retail to offer its products in the market, and a new structure which serves directly the farmers. The results also point out that the waste of hybrid corn seeds in Brazil is related to supply chain structure. The presence of a numerous immediate tier customers and the lack of collaborative working between the processor and the retail blocks the processors demand visibility. The activities that form the demand management are made mainly by the processor, with a functional work structure and showing a low level of integration with the retail. The lack of information about the demand results in seeds production plan based on the stores orders, raising the distortion on the demand estimate, creating the bullwhip effect. Besides that, it leads the seeds processor to push inventory forward based on forecasting. The push inventory raises the level of the stocks and causes a risk of incorrect stocks in the retail, mainly because it is an innovative product with hard forecasting. These problems were not verified in the structure that serves the farmer directly. In this case, there is a higher integration of the demand management process, what allows a reduction of wastes.